2019
DOI: 10.1002/ps.5476
|View full text |Cite
|
Sign up to set email alerts
|

Is DEET a dangerous neurotoxicant?

Abstract: Controversies surrounding the safety of N,N-diethyl-meta-toluamide (DEET) when used as an insect repellent are centered around conflicting findings in the scientific literature and inaccurate reporting in the public media. Lethal cases of DEET poisoning are few, and usually due to deliberate or other overdoses that ignore product label instructions. Deleterious effects of DEET typically involve skin reactions and even when encephalopathies, such as seizures, occur they often abate without sequelae. Recent mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…Firstly, there has been minimal research done on available alternatives to the proposed practices. Taking the case of insect repellents, numerous studies are available to prove the efficacy [ 59 , 60 , 61 , 85 ] and explore the potential safety concerns [ 86 , 87 , 88 ] of DEET. However, the strength of research supporting the repellence of natural alternatives like plant oils is variable [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, there has been minimal research done on available alternatives to the proposed practices. Taking the case of insect repellents, numerous studies are available to prove the efficacy [ 59 , 60 , 61 , 85 ] and explore the potential safety concerns [ 86 , 87 , 88 ] of DEET. However, the strength of research supporting the repellence of natural alternatives like plant oils is variable [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the safety of DEET has yielded conflicting findings. While some studies demonstrate potential harms such as the pro-angiogenic properties of DEET [ 86 ], others suggest that DEET imposes minimal to no evident health risks under proper usage [ 87 ], even when applied on vulnerable groups such as children and pregnant women [ 88 ].…”
Section: Figurementioning
confidence: 99%
“…Our results suggest that although insect repellents on clothes/skin were not associated with birth weight and length, this pesticide may suppress child body growth one month after birth. Although DEET has been considered relatively safe for humans [ 23 ], a study observed fetal birth weight loss in the litters of pregnant rats exposed to high doses of DEET [ 24 ]. The impact of the effects of DEET on human thyroid hormone remains unclear, and the association between DEET exposure and human child body sizes and growth trajectories requires careful interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…N,N-diethyl-3-methylbenzamide (DEET) has been considered one of the most effective repellents [ 4 ]. While there have been reports due to toxic effects on children and pregnant women, the harmful effects are minimized when label instructions are properly followed [ 5 , 6 , 7 ]. Research interest to find new natural anti-mosquito agents has grown in the last decades [ 8 ].…”
Section: Introductionmentioning
confidence: 99%